A Comprehensive Systematic Review of CO2 Reduction Technologies in China’s Iron and Steel Industry: Advancing Towards Carbon Neutrality - Tianshu Hou; Yuxing Yuan; Hongming Na (Energies)
The iron and steel industry, a major energy consumer, faces significant pressure to reduce CO2 emissions. As the world’s largest steel producer, China must prioritize this sector to meet its carbon neutrality goals. This study provides a comprehensive review of various carbon reduction technologies to drive decarbonization in the steel industry. China’s iron and steel sector, which accounted for approximately 15% of the country’s total CO2 emissions in 2022, predominantly relies on coke and coal combustion. This study provides a comprehensive review of a variety of carbon reduction technologies to advance decarbonization in the iron and steel industry. This study categorizes carbon reduction technologies in the steel sector into low-carbon, zero-carbon, and negative-carbon technologies. Low-carbon technologies, which are the most widely implemented, are further divided into energy structure adjustment, material structure adjustment, energy efficiency improvement technologies, etc. This study specifically reviews dry quenching technology, high-scale pellet technology for blast furnace, and top pressure recovery turbine power generation technology. As a zero-carbon technology, hydrometallurgy is a central focus of this study and a key area of research within China’s iron and steel industry. While negative-carbon technologies are primarily centered around carbon capture, utilization technologies are still in early stages. By presenting the latest advancements, this study offers valuable insights and guidance to facilitate the iron and steel industry’s transition to a low-carbon future, crucial for mitigating global climate change.